Normal Neurodevelopment and Fertility in Juvenile Male Rats Exposed to Polyethylene Glycol Following Dosing With PEGylated rFIX (Nonacog Beta Pegol, N9-GP): Evidence from a 10-Week Repeat-Dose Toxicity Study. (December 2022) - Jensen, Vivi F. H.; Schefe, Line H.; Jacobsen, Helene; Mølck, Anne-Marie; Almholt, Kasper; Sjögren, Ingrid; Dalsgaard, Charlotte M.; Kirk, Rikke K; Benie, Andrew J.; Petersen, Bent O.; Kyhn, Mette S.; Overgaard, Anne J.; et al.
N9-GP/Rebinyn ® /Refixia ® is an approved PEGylated (polyethylene glycol-conjugated) recombinant human factor IX intended for prophylactic and/or on-demand treatment in adults and children with haemophilia B. A juvenile neurotoxicity study was conducted in male rats to evaluate effects on neurodevelopment, sexual maturation, and fertility following repeat-dosing of N9-GP. Male rats were dosed twice weekly from Day 21 of age with N9-GP or vehicle for 10 weeks, followed by a dosing-free recovery period for 13 weeks and terminated throughout the dosing and recovery periods. Overall, dosing N9-GP to juvenile rats did not result in any functional or pathological effects, as measured by neurobehavioural/neurocognitive tests, including motor activity, sensory function, learning and memory as well as growth, sexual maturation, and fertility. This was further supported by the extensive histopathologic evaluation of brain tissue. Exposure and distribution of polyethylene glycol was investigated in plasma, choroid plexus, cerebrospinal fluid, and brain sections. PEG did not cross the blood brain barrier and PEG exposure did not result in any effects on neurodevelopment. In conclusion, dosing of N9-GP to juvenile rats did not identify any effects on growth, sexual maturation and fertility, clinical and histological pathology, or neurodevelopment related to PEG exposure and supports the prophylactic use of N9-GP in children.